Anti-Inflammatory and Antioxidative N-Acetyldopamine Dimers from Adult Vespa velutina auraria Smith - Liu, Chao-He; Pang, Xiu-Qing; Yu, Qun; Zhang, Wei; Xu, Jing-Lei; Ma, Yu-Chen; Huang, Lei; Huang, Geng; Wang, Jia-Peng; Xiao, Huai; Ding, Zhong-Tao (Molecules (Basel, Switzerland), 2024)
One undescribed fatty glyceride (1), two unreported N-acetyldopamine dimers (2 and 3), and four known structurally diverse N-acetyldopamine dimers were isolated from adult Vespa velutina auraria Smith. Their structures were elucidated based on a comprehensive analysis of spectroscopic data, HRESIMS, and NMR calculations with ML_J_DP4, and the absolute configurations of 2 and 3 were determined via ECD calculations. Regarding their bioactivities, compounds 5 and 6 can inhibit the production of NO. Moreover, compounds 3, 5 and 7 showed stronger antioxidant activity than the positive control (VC) at 14 μg/mL. A network pharmacology study was used to explore the potential bioactive mechanisms. In addition, a docking study of anti-inflammatory and antioxidative compounds was also performed.